Port-site Metastasis from Gall Bladder Adenocarcinoma with Squamous Differentiation Following Laparoscopic Cholecystectomy: A Rare Case Report - Kafil Akhtar; Asfa Shams; Sadaf Abbas; Suhailur Rehman (Asian Pacific Journal of Cancer Care, 2023)
Port site cutaneous metastasis of gallbladder cancer is an exceedingly infrequent phenomenon with very few cases reported in the past. Herein, we report a case of port site cutaneous metastases of gallbladder adenocarcinoma in a 57 years old female. Physical examination revealed a non healing ulcer in the epigastric region. FNA was suggestive of poorly differentiated carcinoma. Biopsy demonstrated atypical cells. Immunohistochemical analysis showed diffuse cytoplasmic staining with CK 7 and p63 showed focal nuclear positivity in tumour cells. This confirmed the diagnosis of metastastatic gall bladder adenocarcinoma with squamous differentiation. Diagnosis in such a case can be very challenging as the differential of primary cutaneous malignancies should also be kept in mind.